How do we think the COVID-19 crisis will affect our careers (if any remain)? - Stijn Baert; Louis Lippens; Eline Moens; Philippe Sterkens; Johannes Weytjens (Global Labor Organization (GLO), 2020)
This study is the first in the world to investigate the expected impact of the COVID-19 crisis on career outcomes and career aspirations. To this end, highquality survey research with a relevant panel of Belgian employees was conducted. About 21% of them fear losing their jobs due to the crisis—14% are concerned that they will even lose their jobs in the near future. In addition, 26% expect to miss out on promotions that they would have received had the COVID-19 crisis not occurred. This fear of a negative impact is higher in vulnerable groups, such migrants. In addition, we observe that many panel members believe they will look at the labour market differently and will have different work-related priorities in the future. In this respect, more than half of the panel members indicate that they have attached more importance to working conditions and work-life balance since the COVID-19 crisis.
Keywords: 330; COVID-19; careers; employment; career aspirations